Covid-19 Cartooning as Critique: An Analysis of Select Webcomics of Rachita Taneja and Satish Acharya. (2nd July 2020) - Yadav, Neha
Abstract : For Indian citizens, 2020 was not just the year of a global pandemic. It was also the year that brought home the fact that the world's largest democracy is slowly but surely crumbling under the stewardship of a far-right government that has been stoking communal tensions, eroding civil rights and hollowing out the economy from within. The administration's handling of Covid-19 has been marked by a trademark mixture of cruelty and incompetence: announcing the world's strictest lockdown with no prior notice, resulting in a mass exodus of migrant workers forced to travel hundreds of kilometers on foot from cities to their villages; peddling fake science; vaccination mismanagement, etc. It has been aided in this process by the country's mainstream media that has largely abdicated its adversarial role of holding those in power accountable. Webcomics have stepped into this vacuum to critique the socio-political dimensions of the pandemic through satire, their caricatures shared far and wide on social media and private messaging apps. These webcomics, I argue, have taken up the mantle of editorial cartooning which Victor Navasky has theorised as both routinely trivialised and powerfully subversive. The social media trolling received by Acharya as well as a Supreme Court injunction issued to Taneja testifies to what Navasky calls the peculiarly incendiary power of caricature. In my paper, I offer close readings of the Covid-19 related digital cartoons of Satish Acharya and Rachita Taneja and analyse the ways in which they offer a counter-hegemonic narrative of the pandemic in India.